2022
DOI: 10.3389/fphar.2022.1000278
|View full text |Cite
|
Sign up to set email alerts
|

NQO1 protects against clioquinol toxicity

Abstract: Clioquinol (CQ) was widely used as oral antibiotic before being taken off the market in many countries in 1970, after it was linked to subacute myelo-optic neuropathy (SMON) in Japan, leading to vision loss with many patients left wheelchair-bound. The common pathology of CQ-associated SMON was reproduced in animals but none of the proposed modes of toxicity explained the restriction of CQ-induced SMON to Japan. Given a re-emergence of CQ and related analogues as neuroprotectants, it is crucial to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Recently, on the basis of an in vitro functional assay, Chhetri et al. reported that the loss of function of NQO1 (OMIM: 125860, NM_000903.3) may be associated with the development of SMON (Chhetri et al., 2022 ). In particular, the NQO1 rs1800566 polymorphism (c.559C>T, p. Pro187Ser) (Lienhart et al., 2014 ), which is common in the Japanese population (Table 1 ), may be associated with the development of SMON.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, on the basis of an in vitro functional assay, Chhetri et al. reported that the loss of function of NQO1 (OMIM: 125860, NM_000903.3) may be associated with the development of SMON (Chhetri et al., 2022 ). In particular, the NQO1 rs1800566 polymorphism (c.559C>T, p. Pro187Ser) (Lienhart et al., 2014 ), which is common in the Japanese population (Table 1 ), may be associated with the development of SMON.…”
Section: Introductionmentioning
confidence: 99%